Modeling of Drift Effects on Solar Tower Concentrated Flux Distributions - Luis O. Lara-Cerecedo; Isaias Moreno-Cruz; Nun Pitalúa-Diaz; Camilo A. Arancibia-Bulnes (International Journal of Photoenergy)
A novel modeling tool for calculation of central receiver concentrated flux distributions is presented, which takes into account drift effects. This tool is based on a drift model that includes different geometrical error sources in a rigorous manner and on a simple analytic approximation for the individual flux distribution of a heliostat. The model is applied to a group of heliostats of a real field to obtain the resulting flux distribution and its variation along the day. The distributions differ strongly from those obtained assuming the ideal case without drift or a case with a Gaussian tracking error function. The time evolution of peak flux is also calculated to demonstrate the capabilities of the model. The evolution of this parameter also shows strong differences in comparison to the case without drift.